(untitled) (Nexo Revista Científica, 2021)
Aluminum alloys and composite materials are used in the body structures of modern passenger railway cars, which required the use of new manufacturing technologies: extrusion, pultrusion, etc. The use of new materials and new production technologies is changing the design requirements of passenger rail cars. The use of computer-aided design systems, in particular, SolidWorks Simulation, allows you to optimize the profile of cellular panels used in the construction of the body of a passenger railway car and obtained by extrusion or 3-D printing. Purpose of this work is to optimize the design stage of the enclosing structures of the body of a passenger railway car made of cellular profile panels, which can significantly reduce the heat transfer coefficient of the body walls and their mass, as well as provide the necessary strength conditions. Optimal profile of the vacuum panel, consisting of two rows of hexagonal cells, provides, according to calculations, the value of the specific thermal resistance R = 2.922 (m2 K)/W, which is 16.5% more than that of the existing body structure of a passenger rail car.